2018
DOI: 10.2147/ijn.s184262
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal drug delivery in an in vitro 3D bone marrow model for multiple myeloma

Abstract: PurposeLiposomal drug delivery can improve the therapeutic index of treatments for multiple myeloma. However, an appropriate 3D model for the in vitro evaluation of liposomal drug delivery is lacking. In this study, we applied a previously developed 3D bone marrow (BM) myeloma model to examine liposomal drug therapy.Material and methodsLiposomes of different sizes (~75–200 nm) were tested in a 3D BM myeloma model, based on multipotent mesenchymal stromal cells, endothelial progenitor cells, and myeloma cells c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…The 3D model was highly superior when compared to a similar 2D approach and considered appropriate for clinical testing as it was successfully applied to 13 patients’ samples. The same 3D model was also implemented to test liposomal delivery of drugs, such as doxorubicin and bortezomib [ 61 ]. This study showed increased cytotoxic effects of loaded liposomes against MM cells compared with free drugs, using either an MM cell line or primary BM-derived cells.…”
Section: 3d Ex Vivo Platforms Using Gel Scaffoldsmentioning
confidence: 99%
“…The 3D model was highly superior when compared to a similar 2D approach and considered appropriate for clinical testing as it was successfully applied to 13 patients’ samples. The same 3D model was also implemented to test liposomal delivery of drugs, such as doxorubicin and bortezomib [ 61 ]. This study showed increased cytotoxic effects of loaded liposomes against MM cells compared with free drugs, using either an MM cell line or primary BM-derived cells.…”
Section: 3d Ex Vivo Platforms Using Gel Scaffoldsmentioning
confidence: 99%
“…It was found that the 3D model enabled superior analysis of the homing behavior of the TEGs, in addition to improved evaluation of the on‐ and off‐target effects of this potential therapy . Braham and colleagues further employed this Matrigel model to examine liposomal drug delivery in the context of myeloma, which showed increased cytotoxic effects of bortezomib and doxorubicin as compared with free drugs . To study oxygen and drug gradients, drug resistance, and myeloma–microenvironment interaction, de la Puente and colleagues created 3D tissue‐engineered BM cultures derived from BM supernatant of MM patients.…”
Section: Bone Cancer Applications Of 3d Bone Modelsmentioning
confidence: 99%
“…(88) Braham and colleagues further employed this Matrigel model to examine liposomal drug delivery in the context of myeloma, which showed increased cytotoxic effects of bortezomib and doxorubicin as compared with free drugs. (89) To study oxygen and drug gradients, drug resistance, and myeloma-microenvironment interaction, de la Puente and colleagues created 3D tissue-engineered BM cultures derived from BM supernatant of MM patients. Their study found that this 3D model more accurately simulated the tumor interaction with the microenvironment, and that drug resistance was induced at a higher rate than in 2D or commercial 3D systems.…”
Section: Multiple Myelomamentioning
confidence: 99%
“…Given this fact, 3D models of MM cells inside native‐mimicking microenvironments display unique advantages in terms of establishing proper cell functions and associated signaling pathways, making the evaluations of drug effects more efficient and accurate in a (patho)physiologically relevant context. [ 17–19 ]…”
Section: Introductionmentioning
confidence: 99%
“…Given this fact, 3D models of MM cells inside native-mimicking microenvironments display unique advantages in terms of establishing proper cell functions and associated signaling pathways, making the evaluations of drug effects more efficient and accurate in a (patho)physiologically relevant context. [17][18][19] Recently, 3D bioprinting has been explored extensively for forming well-organized volumetric structures of human tissues and organs, [20] which has also found increasing utility in tumor modeling in vitro. [21,22] For example, we [23][24][25][26][27][28] and others [29][30][31] have previously reported the multichannel coaxial extrusion systems for bioprinting multilayered tubular tissues for various application scenarios.…”
Section: Introductionmentioning
confidence: 99%